أثر درجة تنويع محفظة القروض على مستوى الأمان المصرفي ( دراسة تطبيقية على عينة من المصارف التجارية السورية الخاصة) - محمد رامي (Latakia University Journal - Economic and Legal Sciences Series, 2018)
تهدف هذه الدراسة إلى دراسة العلاقة بين درجة تنويع محفظة القروض ومستوى الأمان المصرفي في المصارف التجارية السورية الخاصة، ولتحقيق ذلك تم جمع البيانات اللازمة من التقارير السنوية المنشورة للمصارف من مواقعها الإلكترونية وعددها (6) مصارف والتي مثلت عينة الدراسة عن الفترة الممتدة من (2009 – 2016)، تمثل المتغير المستقل بدرجة تنويع محفظة القروض وتم قياسه باستخدام مؤشر هيرفندال هيرشمان (Herfindal - Hirschman )، والمتغير التابع بمستوى الأمان المصرفي وتم قياسه بنسبة حقوق الملكية. أظهرت نتائج الدراسة وجود تباين في أثر درجة تنويع محافظ قروض المصارف التجارية السورية الخاصة على مستوى الأمان المصرفي، حيث يوجد أثر إيجابي لدرجة التنويع في مصرف عودة سورية والمصرف العربي سورية على مستوى الأمان المصرفي، في حين أنه لا يوجد أثر معنوي لدرجة التنويع في مصرف بيمو السعودي الفرنسي، مصرف سورية والمهجر، المصرف الدولي للتجارة والتمويل، مصرف بيبلوس سورية على مستوى الأمان المصرفي. The purpose of this study is to study the relationship between the degree of diversification of loan portfolios and the level of banking safety in the private Syrian commercial banks. In order to achieve this, the necessary data were collected from the published annual reports of banks from their six websites which represented the study sample for the period (2009-2016) , The independent variable represented the degree of diversification of the loan portfolio and was measured using the Herfindal-Hirschman index, and the dependent variable at the level of bank security measured by the equity ratio. The results of the study showed that there is a difference in the degree of diversification of the portfolios of private commercial banks in Syria at the level of banking safety. There is a positive effect of diversification in the Bank of Syria and the Arab Bank of Syria on the level of banking safety. Bank of Syria and Overseas, International Bank for Trade and Finance, Byblos Bank of Syria at the level of banking security.